Corporate governance practices and bank performance in Asian emerging market post-financial calamity/ Hasroleffendy Hassan... [et al.] - Hassan, Hasroleffendy; Mohd Hanafiah, Mohd Hafiz; Abu Hassan, Mohamad Hanif; Shaharudin, Mohd Rizaimy (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study assessed the influence of bank corporate governance attributes, including risk governance, board governance, disclosure and transparency governance, together with bank restructuring on bank performance within the context of Asia's emerging markets from 2011 to 2015, following the 2007 financial crisis. This study leveraged a dataset comprising 109 banks, totaling 545 observations across eight countries, via panel data analysis techniques. Notably, the analysis revealed that risk governance mechanisms significantly and positively affected the overall performance of the banks. Furthermore, both board governance and disclosure and transparency governance made substantial contributions to improving the banks' performance. However, there was a negligible connection between bank restructuring measures and Net Interest Margin (NIM), while most control variables displayed a significant impact on bank performance. In light of these findings, this study advocates for the use of corporate governance enhancements by bank management to enhance their performance. This recommendation could be regulated through the implementation of reforms within the corporate governance codes and guidelines for banking institutions in respective countries. Furthermore, this paper offers a unique empirical model for studying the relationship between corporate governance and bank performance, providing valuable insights and contributing to the existing body of knowledge in this domain.